End-User Computing Satisfaction (EUCS) Model: Implementation of Learning Management System (LMS) on Students Satisfaction at Universities - Andi Padalia; Taufiq Natsir (Three E Science Institute, 2022)
The purpose of this research is to find out the extent to which user satisfaction with the Learning Management System (LMS) service is so that it can provide better service and can satisfy/meet the needs of its users by measuring user satisfaction with information systems using the End-User Computing Satisfaction (EUCS) model approach. The researcher adopted the EUCS model developed by Doll and Torkzadeh regarding the satisfaction of end users of information systems. Related to the level of contentment experienced by end users of information systems, the researcher chose to implement the EUCS model that Doll and Torkzadeh had developed. The collected research samples came from a total of two hundred (200) students enrolled in the Arts, Drama, Dance, and Music Education Study Program in batches of 2021 and 2022. Confirmatory Factor Analysis (CFA), a subset of the Structural Equation Modeling (SEM) method, was used to analyze this research project's data. User satisfaction will also affect if the variable of ease of use in learning applications used by students is easy to access and can be accessed anywhere and anytime. This study found that students were highly satisfied with the Application of LMS in the learning process. It was also found that the five EUCS factors significantly increased satisfaction with learning technology.